2007
DOI: 10.1371/journal.pone.0000592
|View full text |Cite
|
Sign up to set email alerts
|

ASSET (Age/Sex Standardised Estimates of Treatment): A Research Model to Improve the Governance of Prescribing Funds in Italy

Abstract: BackgroundThe primary objective of this study was to make the first step in the modelling of pharmaceutical demand in Italy, by deriving a weighted capitation model to account for demographic differences among general practices. The experimental model was called ASSET (Age/Sex Standardised Estimates of Treatment).Methods and Major FindingsIndividual prescription costs and demographic data referred to 3,175,691 Italian subjects and were collected directly from three Regional Health Authorities over the 12-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This observational, cross-sectional study was part of the ASSET (Age and Sex Standardised Estimates of Treatment) project [16], a pharmacoeconomic and pharmacoepidemiological study. This analysis focused on data from the Regional Health Departments of Basilicata (a southern Italian region with almost 600,000 inhabitants) and Marche (a central Italian region with almost 1.5 million inhabitants), with a population of slightly more than two million subjects (ASSET population), 1738 general practitioners (GPs) and 244 family paediatricians (FPs).…”
Section: Methodsmentioning
confidence: 99%
“…This observational, cross-sectional study was part of the ASSET (Age and Sex Standardised Estimates of Treatment) project [16], a pharmacoeconomic and pharmacoepidemiological study. This analysis focused on data from the Regional Health Departments of Basilicata (a southern Italian region with almost 600,000 inhabitants) and Marche (a central Italian region with almost 1.5 million inhabitants), with a population of slightly more than two million subjects (ASSET population), 1738 general practitioners (GPs) and 244 family paediatricians (FPs).…”
Section: Methodsmentioning
confidence: 99%
“…Among the factors related to the varying prescription activity, age of patients was most often factored into analyses of variation [ 37 ], although age alone did not account for enough variation to develop an accurate model for predicting prescribing rates [ 38 ]. It was shown that age and gender accounted for approximately 25% of variation [ 39 , 40 ] and additional demographic characteristics (e.g. mortality rates) up to 51% [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of some English studies analysing the influence of such variables on drug prescription in primary health care show that they influence prescription patterns [2][3][4][5][6][7] and cost [5][6][7]. GPs' prescribing decisions have come under increased scrutiny, above all in those Italian regions where health care deficits remain high, and there is considerable pressure to contain costs by prescribing cost-effectively [8][9][10][11]. Thus, knowledge of prescription patterns is important in order to improve, evaluate and make adjustments to the pharmaceutical formulary [12].…”
Section: Introductionmentioning
confidence: 99%